Efficacy of Wharton Jelly Mesenchymal Stromal Cells infusions in moderate to severe SARS-Cov-2 related acute respiratory distress syndrome: a phase 2a double-blind randomized controlled trial - Pochon, Cécile; Laroye, Caroline; Kimmoun, Antoine; Reppel, Loic; Dhuyser, Adéle; Rousseau, Hélène; Gauthier, Mélanie; Petitpain, Nadine; Chabot, Jean-François; Valentin, Simon; de Carvalho Bittencourt, Marcelo; Peres, Michael; et al. (Frontiers in Medicine, 2023)
Background The COVID-19 pandemic caused a wave of acute respiratory distress syndrome (ARDS) with a high in-hospital mortality, especially in patients requiring invasive mechanical ventilation. Wharton Jelly-derived Mesenchymal Stromal Cells (WJ-MSCs) may counteract the pulmonary damage induced by the SARS-CoV-2 infection through pro-angiogenic effects, lung epithelial cell protection, and immunomodulation. Methods In this randomized, double-blind, placebo-controlled phase 2a trial, adult patients receiving invasive mechanical ventilation for SARS-CoV-2 induced moderate or severe ARDS were assigned to receive 1 intravenous infusion of 1 × 106 WJ-MSCs/kg or placebo within 48 h of invasive ventilation followed by 2 infusions of 0.5 × 106 WJ-MSCs/kg or placebo over 5 days. The primary endpoint was the percentage of patients with a PaO2/FiO2 > 200 on day 10. Results Thirty patients were included from November 2020 to May 2021, 15 in the WJ-MSC group and 15 in the placebo group. We did not find any significant difference in the PaO2/FiO2 ratio at day 10, with 18 and 15% of WJ-MSCs and placebo-treated patients reaching a ratio >200, respectively. Survival did not differ in the 2 groups with a 20% mortality rate at day 90. While we observed a higher number of ventilation-free days at 28 days in the WJ-MSC arm, this difference was not statistically significant (median of 11 (0–22) vs. 0 (0–18), p = 0.2). The infusions were well tolerated, with a low incidence of anti-HLA alloimmunization after 90 days. Conclusion While treatment with WJ-MSCs appeared safe and feasible in patients with SARS-CoV2 moderate or severe ARDS in this phase 2a trial, the treatment was not associated with an increased percentage of patients with P/F > 200 at 10d, nor did 90 day mortality improve in the treated group. Clinical trial registration https://beta.clinicaltrials.gov/study/NCT04625738, identifier NCT04625738.